Terrestrial heat flow and its geodynamic implications in the northern Songliao Basin, Northeast China. Issue 2 (13th December 2021) - Shi, Yizuo; Jiang, Guangzheng; Shi, Shangming; Wang, Zecheng; Wang, Shejiao; Wang, Zhuting; Hu, Shengbiao
SUMMARY: Heat flow data are essential for understanding lithospheric dynamics. As a petroliferous basin, a large number of boreholes have been drilled during hydrocarbon exploration and production in the northern part of Songliao Basin, Northeast China. Meanwhile, the data on crustal structures, core samples and formation temperatures have been accumulated, which provide an opportunity for understanding the thermal state of the basin. Based on the temperature data from both Drilling Stem Test and continuous steady-state logging profiles, together with the systematic analysis of the thermal properties of rock samples, we present a new heat flow map of the northern Songliao Basin with significantly increased number of heat flow sites. The northern Songliao Basin is characterized by relatively high geothermal gradients and high heat flow for sedimentary basins. The heat flow values range from 44.4 to 95.0 mW m –2 with an average of 67.2 ± 12.8 mW m –2, and the geothermal gradients range from 21 to 59 °C km –1 with an overall average of 41.7 °C km –1 . Heat production from sedimentary covers accounts for about 4.5 mW m –2 at the site of Well SK-2. Furthermore, based on the crustal structures revealed by previous seismic studies, lithospheric thermal structures are analysed and compared among different structural units of the basin. A thinned thermal lithosphere with a thickness of ∼65 km is found beneath the Central downwarp and the Southeast uplift in which a large part of the heat flow is mantle derived. The Western Slope exhibits a moderate heat flow value and a thicker thermal lithosphere with thickness greater than 110 km. From the perspective of the geothermal state of the lithosphere, the regional geodynamics related to the Mesozoic lithosphere stretching and the subduction of the Pacific Plate are discussed.